PENGGUNAAN BERBAGAI MACAM MEDIA TUMBUH DALAM PEMBUATAN BIBIT INDUK JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Putra Utama; Dusep Suhendar; Lisa Herlisa Romalia (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2013)
This experiments objective to determine the effect of the used of various growth substrates to make stock culture of oyster musroom spawn on the growt of mycelium. The experiments was conducted at the Faculty of Agriculture Agroekoteknologi Universitas Sultan Ageng Tirtayasa Serang Banten Province for the manufacture of pure cultures and Laboratory Pemuda Aktif Sejahtera, Village Sukamekarsari, Kalanganyar, Lebak, for making spawn in May until July 2011. The experiments used Randomized Control Group Design with seven treatments (A: corn , B: green beans, C: grain, D: millet, E: albasiah sawdust, F: mahoni sawdust, G: kecapi sawdust) and five replications. Results obtained from research the use of various growth substrates were significantly different age parameter begins to form mycelium, mycelium growth and percentage growth rete of mycelium.